Fe evaluation of thermal property of mould wall material for investment casting and the effect of layers on the hardness of the casting product - Phuan, Yoong Jiann (Universiti Teknologi Malaysia, 2004)
This thesis is aimed to investigate and establish a correlation between the mold wall thickness and the mechanical properties of the non-ferrous alloy in investment casting. Mold material of the fine stucco system is investigated. For the investigation proposes, four molds with different thicknesses are established: 5, 7, 9, and 11 layers. Pouring temperature is set to 660Â°C. After pouring, the temperatures of the outer and inner wall of the mold materials is recorded until the temperature reach the steady state condition. Finite element analysis based on a plane strain assumption is employed to evaluate the thermal conductivity k, of the mold material with different thicknesses,based on the experimental steady state temperature of the inner and outer surface of the mold material. The mechanical properties of the casting materials are investigated by observing the microstructure and performed Vickers Hardness Test on the casting specimens. In the findings, the thermal conductivity k, of the mold materials is almost the same. The percentage of the silicon flakes for the cast product is decreased with the increasing of mold wall thickness. The Vickers Hardness also decreased with the increasing of mold wall thickness.